Control of Menopausal Transition through Physical Exercises - Wiacek, Magdalena (Current Women's Health Reviews, 2013)
Background: A consensus among women is that the menopause is imminently associated with a reduction in the level of physical fitness, which is associated with an increase in body-weight and emotional disturbances. Such an understanding of the menopausal transition is strengthened by plethora of scientific reports on the biology of the menopause. However, there is a dearth of data on a means of modulation, other than pharmaceutical, of these detrimental phenomena. Discussion: The majority of scientific reports indicates that menopause and/or ageing is associated with an increase in Body Mass Index (BMI), Waist Circumference (WC), Total Cholesterol (TC), Tri-glyceride (TG), High-Density Cholesterol (HDL-C), Low-Density Cholesterol (LDL-C), Luteinizing hormone (LH), and Follicle Stimulation hormone (FSH) levels. Additionally, recent reports indicated that menopausal transition is also associated with changes in blood pressure (BP), serum uric acid levels (SUA), and serum creatinine (SCR). It has been shown that during the menopause, an interplay of these homeostasis regulating parameters adversely influences health-related quality of life (HQoL). Currently, physical exercises are considered as an alternative to pharmaceutical means of positive modulation of agedependent physiological changes. Summary: Through a combination of the results of scientific reports on an influence of physical exercises on the set of physiological parameters, I have established that physical exercises, encompassing endurance, aerobic, and strength exercises, may be used as a happy medium for preserving a high level of HQoL in ageing and menopausal women. However, I postulate that physical exercises applied in this regard should not be focused on an increase in a fitness level, expressed as an increase in a maximal oxygen capacity, but instead on a abate of the total body fat.
Keywords: serum lipids